Dyadic examination of rumination and depressive symptoms in Chinese heterogeneous young couples: the differential role of gender - Liu, Xiaoyu; Zhou, Anji; Jin, Zhuyun; Han, Zhuo Rachel; Qian, Jing; Wang, Hui (Frontiers in Psychiatry, 2025)
IntroductionThe relationship between rumination and depressive symptoms has been extensively studied over the past two decades. However, few studies have explored how rumination contributes to depressive symptoms within the context of heterogeneous romantic relationships, particularly regarding potential gender differences in these effects. The present study aims to investigate whether rumination is related to four key factors of depressive symptoms (i.e., depressed affect, positive affect, somatic and retarded activity, interpersonal distress) both on the intrapersonal and interpersonal levels among young couples.MethodsParticipants were 148 Chinese young couples (N = 296; males: M age = 21.94 years, SD = 2.40 years; females: M age = 21.62 years, SD = 2.26 years). Couples completed self-reported questionnaires assessing rumination and depressive symptoms separately, using the Ruminative Response Scale (RRS) and the Center for Epidemiologic Studies Depression Scale (CES-D).ResultsThe results of a series of actor-partner interdependence models (APIM) showed that, on the intrapersonal level, rumination was positively and significantly associated with an individual’s own depressed affect, somatic and retarded activity, and interpersonal distress. On the interpersonal level, higher levels of rumination in males were associated with increased depressed affect and interpersonal distress in their female partners. However, no such partner effect was observed for male partners of ruminative females.ConclusionsThese findings suggest that females in romantic relationships, as compared to males, may be more susceptible to the influence of their male partners’ rumination. This study is among the firsts to demonstrate the gender-specific effect in the relationship between rumination and depressive symptoms in young couples.